The Implementation of Marketing Mix for SME - Paundanan, Olfa Ningsi; Sutomo, Maskuri; Syarifuddin, Umar; Asriadi, A. (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
Small and Medium Industries (SMIs) in the food sector play an important role in Indonesia's economic growth, but still face significant challenges in maintaining competitiveness amid increasingly fierce market competition and changes in consumer behavior. This study aims to analyze the implementation of the marketing mix (product, price, promotion, and distribution) at Sekotak Dari Dapur Bu' Sarhan SMI in Palu City, which is known for its innovative fishball products. The research method used is descriptive qualitative with a case study approach, involving participatory observation, in-depth interviews, and documentation with the primary informants, the owner and employees. The results show that local fish-based product innovation, cost-based pricing, and promotion through social media are the main factors in building the uniqueness and competitiveness of this SME. However, digital audience engagement is still low, and product distribution is limited to certain areas, so more creative promotion strategies and logistics partnerships are needed to expand the market. This research confirms the importance of adaptive and innovative marketing mix management. It provides practical recommendations for food SMEs to improve competitiveness through product innovation, price optimization, strengthening digital promotion, and expanding distribution networks. The findings are expected to be a reference for developing sustainable food SME marketing strategies in the digital era.